Carbodicarbenes and Striking Redox Transitions of their Conjugate Acids: Influence of NHC versus CAAC as Donor Substituents. Issue 2 (15th November 2022) - Dolai, Ramapada; Kumar, Rahul; Elvers, Benedict J.; Pal, Pradeep Kumar; Joseph, Benson; Sikari, Rina; Nayak, Mithilesh Kumar; Maiti, Avijit; Singh, Tejender; Chrysochos, Nicolas; Jayaraman, Arumugam; Krummenacher, Ivo; et al.
Abstract: Herein, a new type of carbodicarbene (CDC) comprising two different classes of carbenes is reported; NHC and CAAC as donor substituents and compare the molecular structure and coordination to Au(I)Cl to those of NHC‐only and CAAC‐only analogues. The conjugate acids of these three CDCs exhibit notable redox properties. Their reactions with [NO][SbF6 ] were investigated. The reduction of the conjugate acid of CAAC‐only based CDC with KC8 results in the formation of hydrogen abstracted/eliminated products, which proceed through a neutral radical intermediate, detected by EPR spectroscopy. In contrast, the reduction of conjugate acids of NHC‐only and NHC/CAAC based CDCs led to intermolecular reductive (reversible) carbon–carbon sigma bond formation. The resulting relatively elongated carbon–carbon sigma bonds were found to be readily oxidized. They were, thus, demonstrated to be potent reducing agents, underlining their potential utility as organic electron donors and n‐dopants in organic semiconductor molecules. Abstract : Structures and coordination behavior of carbodicarbenes bearing three possible combinations of N‐heterocyclic carbene (NHC) and cyclic(alkyl)(amino)(carbene) (CAAC) are compared. The strikingly different redox transitions of their conjugate acids are also reported.